L–Cysteine Modulated ZIF for Deriving Nitrogen‐Doped Porous Carbon: A Highly Efficient and Stable Electrocatalyst for Oxygen Reduction Reactions. Issue 10 (9th March 2022) - Gan, Xingyu; Wang, Yun; Guo, Xinjie; Wang, Fengxiang; Mao, Guojiang; Lv, Xiaoxia; Wang, Hua
Abstract: Zeolitic Imidazolate Frameworks (ZIFs) derived nitrogen‐doped porous carbon (NPC) materials have been proposed as promising metal‐free electrocatalysts for oxygen reduction reactions (ORR). Herein, we report a strategy to control the morphology of ZIF‐8 and ZIF material‐derived NPC materials by the amount of L‐cysteine. The prepared NPC electrocatalysts exhibit different morphologies and ORR properties. The best of these catalysts exhibited a nanosheet‐like morphology with an onset potential of 0.95 V and a half‐wave potential of 0.87 V in alkaline media, which are comparable to those of commercial Pt/C (20 wt%) catalysts. In addition, this catalyst exhibited high stability and methanol resistance. This work not only reveals the effect of L‐cysteine amount on the growth process of ZIF, but also provides a strategy for designing various excellent catalysts in the fuel cell field. Abstract : L‐cysteine as structure directing agents and zinc acetate as the metal source, distinct morphological ZIF materials were prepared in water medium. Nitrogen doped porous materials derived from these ZIF materials partially inherit their morphology and exhibit distinct ORR electrocatalytic performance. NPC‐2 shows nano‐sheets morphology and exhibits excellent ORR catalytic ability rival commercial Pt/C, good stability and methanol resistance.